Technology Transfer and Risks of Knowledge Leakages Through Training Activities: An Assessment in Sovereign Industries - Coadour, Damien; Droff, Josselin; Bellais, Renaud (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
This paper assesses risks of knowledge leakage associated with training in technology transfers. Today states want to master sovereign technologies. As a consequence, exporting firms have adapted their offers to respond to customers’ requests and provide training in technology transfer contracts. We have recorded the perception of trainers regarding risks of knowledge leakage associated with training activities. Due to different interpretations of technology transfers and related risks, trainers’ assessment of knowledge leakages is not homogeneous in the training process. A typology of trainers and their typical behaviors in professional situations is proposed and leads to recommendations to mitigate knowledge leakages.